Electrochemical Study on the Interaction Between the Macrocyclic Copper(II) and Nickel(II) Complexes and Calf thymus DNA - Bi, Jian-Hong; Li, Meng; Yao, Fu-Hou; Chen, Yan (Asian Journal of Chemistry, 2010)
The interaction of the two tetraazamacrocyclic transition-metal complexes, ML(ClO4)2 (M = Cu2+, Ni2+, L = 5,12-dimethyl-7,14-diphenyl-1,4,8,11-tetraazamacrocyclic-4,11-diene) with calf thymus-DNA (CT-DNA) were studied by cyclic voltammetry. In the presence of CT-DNA, the oxidion peaks of [CuL]2+ and [NiL]2+ shifted to more positive values and the peak current increased significantly. The experimental results indicate that the two complexes could interact with CT-DNA mainly by intercalation binding mode.